EXISTENCE OF MILD SOLUTION FOR HYBRID DIFFERENTIAL EQUATIONS WITH ARBITRARY FRACTIONAL ORDER - Mahmudov, Nazim; Matar, Mohammed M. (Inst Applied Mathematics, 2017)
We investigate in this article the existence problems of mild solutions for hybrid differential equations involving fractional Caputo derivative of arbitrary order. Different types of fixed point theorems are applied for solving the existence problem. An example is given to explain the applicability of all theorems.
Keywords: existence; uniqueness; hybrid fractional differential equations; fixed point theorems